The Impact of the Characteristics of the Board of Directors on Corporate Risk-taking:Evidence from China - Tang, Qiuxuan (2022)
The importance of the board of directors and corporate risk-taking for company growth is gradually being realized as a result of the ongoing advancement of corporate governance.